Biological interpretation of the sporadic sputum smear-positive-culture-negative outcome for patients with tuberculosis undertaking treatments - Luo, Jingjing; Yu, Xia; Dong, Lingling; Huo, Fengmin; Ma, Yifeng; Liang, Qian; Shang, Yuanyuan; Huang, Hairong (Frontiers in Public Health, 2023)
To identify the causes for the smear-positive-culture-negative(S+/C-) outcomes among tuberculosis patients during the treatment courses. The clinical medical records regarding patient category, follow-up bacteriologic examination data and treatment outcomes were investigated. S+/C- was observed in 17.5%(210/1200) of the recruited smear positive patients and more frequently among the patients for which solid culturing was performed instead of liquid culturing (30.4%, 345/1135 V.S. 11.5%, 100/873) (P<0.001, χ2=102.64). Among the 102 S+/C- patients who had follow-up culture performed, 35 (34.3%) had positive culture outcomes. Whereas among the 75 patients with follow-up information for more than 3 months but without supportive bacteriological evidence,53(70.7% ,53/75) had unfavorable prognosis (including relapse and unimproved conditions), and only 22 (29.3%, 22/75) patients had improved conditions. Compared with new cases, retreated cases easily produced S+/C- outcomes and had higher change to cultivate live bacilli afterwards. Among our patients, the sporadic smear positive and culture negative outcome for sputa is more likely associated with technical failures of culture than with dead bacilli, this is especially suitable for LJ medium culture.